Codesign of Social Innovation Projects: Case of the Ñurum District in Panamá - Moreno, Sidia; Briceño, Miguel; Fosstti, Anibal; Martínez, Noris (2019 7th International Engineering, Sciences and Technology Conference (IESTEC), 2019)
The process of social innovation involves 3 major stages: codiseño, coejecucion and monitoring. In this communication, the progress and results of the co-design process of the Project entitled Development of a Participatory Integral System to Improve and Restore Soils and the Productivity of Communities of the District of ÑURUM, which is executed in the Ngobe Buglé Comarca of Veraguas province. The methodology of Participatory Rural Innovation (IRP) with a polytextural approach was applied for the first time in Panama, to address a problem identified by the community itself. The results included: current situation of each context in the studied community, detection of SIR (redundant attempted situations), contextual interaction, disruptive tests and detection of possible overcoming. We also managed to address aspects of governance, requirements and potential of the community and finally innovative solutions were generated that constitute possible subprojects that make up the comprehensive roadmap of social innovation for soil improvement in Cerro Pelado. The experience allowed us to validate that there is a dynamic of social behavior very characteristic of each culture that largely determines the way in which people affected by a problem approach the possible solutions. In this context, CyT groups need to establish effective links with the affected communities to identify, design and implement solutions in a collective and sustainable way.
Keywords: Amérique latine; Co-création; Participatory Rural Innovation